Securities acceptable to the lending banker - Mather, L. C. (London : Waterlow, 1973)
The purpose of this book is to review the practical and legal aspects of securities which are acceptable to the lending banker. The contents have been brought up-to-date in this revised 3rd edition.
Includes index.
usc 05/10/18
Loans
Keywords: Security (Law); Bank loans; Bank loans--Law and legislation; Great Britain